Pengaruh Corporate Social Responsibility (CSR), Komisaris Independen, Dan Intensitas Persediaan Terhadap Penghindaran Pajak - Zaki Faran; Andry Sugeng (CV. ITTC INDONESIA, 2025)
This research aims to determine and provide empirical evidence regarding the influence of Corporate Social Responsibility, Independent Commissioners and Inventory Intensity on Tax Avoidance. This research was conducted on property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. The data used in this research is secondary data. Sampling in this research was carried out using a purposive sampling technique based on predetermined criteria. The research sample obtained is the number of samples to be studied, namely 13 companies with 5 years of observation, from the previous population of 93 companies. The panel data regression method is used as the research methodology in this study. Hypothesis testing was carried out using the E-views Version 12 application. Based on the research results, it shows that corporate social responsibility, independent commissioners and inventory intensity simultaneously influence tax avoidance. then the results of this research also show that corporate social responsibility partially has no effect on tax avoidance, independent commissioners partially have no effect on tax avoidance and inventory intensity partially has an effect on tax avoidance.